Penerapan Model Discovery Learning untuk Mengetahui Peningkatan Hasil Belajar Siswa pada Mata Pelajaran Administrasi Infrastruktur Jaringan di Kelas XI TKJ 1 SMK Negeri 2 Karang Baru - Isniar Handayani (Medan Resource Center, 2022)
The purpose of this study was to obtain information about the effect of discovery learning learning models on student learning outcomes in class XI TKJ 1 SMK Negeri 2 Karang Baru. The population of this study were students of class XI TKJ 1 SMK Negeri 2 Karang Baru, the number of samples was 25 students with 14 males and 11 females in the subject of Network Infrastructure Administration. The implementation of this classroom action research consists of 2 cycles, namely cycle I and cycle II. The results of the analysis in the first cycle showed that the students' learning mastery who was subjected to action from 25 students there were 13 students (53%) who scored above 75, and 12 students (47%) scored less than 75. The percentage of completeness increased. in cycle II where 25 students who were subjected to actions that achieved completeness were 20 students (80%) scored 75 and above and the remaining 5 (20%) scored less than 75 and below and 5 students who had not completed were remedial with the goal so that learning outcomes can achieve completeness.